Carbon dioxide fluxes of cyanobacterial crusts and underlying soil under different precipitation patterns in the Ulan Buh Desert, China - Wang, Lili; Gao, Ying; Cao, Xiaoming; Lu, Weiwei (Frontiers in Environmental Science, 2022)
Cyanobacterial crusts, sensitive to changes in moisture content, are widely distributed in the Ulan Buh Desert. Changes in precipitation patterns due to global climate change are expected to influence the carbon emission and photosynthetic carbon fixation of soil in areas covered with cyanobacterial crust. We assessed how changes in precipitation amount and frequency affect carbon processes. Taking average precipitation amount and frequency in August during the past 30 years as control, we established nine precipitation patterns(three amountsthree frequencies). Net carbon flux (NCF) and dark respiration rate (DRR) of cyanobacterial crust and underlying soil were investigated. Precipitation can stimulate NCF and DRR immediately. With increasing precipitation times, the peak values of NCF and DRR and carbon emissions gradually decreased. Both precipitation amount and frequency significantly affected carbon emissions, but without an interactive effect. Under the same frequency, carbon emissions increased with increasing precipitation amounts. Under the same total precipitation amount, carbon emissions caused by high-frequency events were highest, followed by those of low-frequency precipitation and the control. However, such changes, against the background of a changing global climate, will result in increased carbon emissions of cyanobacterial crusts, suggesting that cyanobacteria should be considered in projections of the future carbon budget.